GOVERNANCE IN OVERCOMING SOCIAL PROBLEMS AT THE COUNTRY BORDER IN ENTIKONG DISTRICT, SANGGAU REGENCY, WEST KALIMANTAN - Udaya Madjid; Irfan Setiawan (Institut Pemerintahan Dalam Negeri, 2021)
This study aims to examine governance in overcoming social problems at state borders in Entikong District, Sanggau Regency, West Kalimantan Province. This study uses a qualitative descriptive approach, where data is collected and analyzed using an interactive model. The results showed that in overcoming social problems in the Entikong area, the government built infrastructure by constructing the Entikong area and its supporting facilities, superstructure development, and community empowerment through human resource development and community cultural development through local wisdom